LINE1 Derepression in Aged Wild-Type and SIRT6-Deficient Mice Drives Inflammation - Simon, Matthew; Van Meter, Michael; Ablaeva, Julia; Ke, Zhonghe; Gonzalez, Raul S; Taguchi, Taketo; De Cecco, Marco; Leonova, Katerina I; Kogan, Valeria; Helfand, Stephen L; Neretti, Nicola; Roichman, Asael; et al. (Cell metabolism, 2019)
Mice deficient for SIRT6 exhibit a severely shortened lifespan, growth retardation, and highly elevated LINE1 (L1) activity. Here we report that SIRT6-deficient cells and tissues accumulate abundant cytoplasmic L1 cDNA, which triggers strong type I interferon response via activation of cGAS. Remarkably, nucleoside reverse-transcriptase inhibitors (NRTIs), which inhibit L1 retrotransposition, significantly improved health and lifespan of SIRT6 knockout mice and completely rescued type I interferon response. In tissue culture, inhibition of L1 with siRNA or NRTIs abrogated type I interferon response, in addition to a significant reduction of DNA damage markers. These results indicate that L1 activation contributes to the pathologies of SIRT6 knockout mice. Similarly, L1 transcription, cytoplasmic cDNA copy number, and type I interferons were elevated in the wild-type aged mice. As sterile inflammation is a hallmark of aging, we propose that modulating L1 activity may be an important strategy for attenuating age-related pathologies.